Cognitive diversity and team creativity: knowledge sharing and sharing information as moderators - Neves, Beatriz João (2021)
Purpose: With the demand for cognitive diversity in the workplace growing every day, it is important to analyse the impacts of that diversity regarding the performance of a team. As creativity being regarded as a major asset in any corporation, it is crucial to inspect the relationship between diversity and creativity, but also the possible moderators between cognitive diversity and creativity. For that reason, in this study knowledge sharing and sharing information are examined as those possible moderators. Methodology: A sample composed of 46 teams, 168 individuals, from different consultancy and auditing companies is used. The data collection was gathered through two surveys, one directed to team leaders and the other aimed for the members of the respective teams. This was done in order to get the viewpoint of the leaders and the members, thus having a more complete and unbiased study. Data at team level were analyzed using a mediation model, macro PROCESS Hayes (2018). Findings: The results obtained show that there is a negative relationship between cognitive diversity and team creativity and that there is no significant proof that knowledge sharing and sharing information work as moderators of that relationship.